Structural studies on antibodies - Dower, S (1979)
﻿ Data from ¹H nuclear magnetic resonance studies on the Fv fragment of protein 315, a Dnp-binding BALB/c mouse lgA(λ2) myeloma protein, have been used to refine a predicted structure of the combining site of the protein. The Dnp-binding subsite in the modified structure is composed of the side chains of three aromatic amino acids Trp 93L, Tyr 34L and 34H. A fourth aromatic amino acid residue is close to the side chain-NH-CH 2 -group, this is Tyr 33 H - The antibody-hapten binding is a simple encounter process, which causes no extensive conformation change in the Fv fragment. A method for paramagnetic structural studies has been devised using Dnp derivatives with cllgophosphate side chains, which create a specific manganese binding site on the Fv fragment-hapten complex. The distances from the bound metal ion to the imidazole side chains of two of the three hlstldine residues of protein 315 have been determined. ¹H nuclear magnetic resonance has been used to study the histidine residues of the Fv fragment of protein 315. It has been shown that one of the three histidine residues (102H) is close to the combining site, but that this residue does not participate directly in binding haptens. 31 P nuclear magnetic resonance studies have shown the presence of a positively charged amino acid side chain near the entrance of the combining site of the Fv fragment. This residue has been identified as Arg 95L. The mode of binding of trini trophenyl derivatives to the Fv fragment has been studied by 1H nuclear magnetic resonance. It is concluded that these haptens, when bound to the Kv fragment, make contacts with the same amino acid side chains as Dnp derivatives.